Dialysate sodium and intradialytic hypotension. Issue 6 (13th July 2017) - Hussein, Wael F.; Schiller, Brigitte
Abstract: Intradialytic hypotension (IDH) is a common complication in hemodialysis, particularly with the time and frequency constraints of standard session delivery in contemporary practice. High intradialytic weight gain (IDWG), high ultrafiltration rates (UFR), and frequent IDH are highly interlinked, and separately or together contribute to the high cardiovascular morbidity and mortality observed in the hemodialysis population. Using a lower concentration of sodium in the dialysate (D‐Na) reduces sodium delivery to the patient during dialysis, and several studies reported the beneficial effect in controlling IDWG, UFR, and hypertension. On the other hand, high dialysate sodium is associated with more hemodynamic benefits in an unstable patient. The resulting sodium loading may, however, induce a vicious cycle of higher IDWG, requiring more rapid ultrafiltration, eventually contributing to intradialytic symptoms and hypotension. In this article, we review the available literature on fixed and profiled dialysate sodium prescriptions, and we recommend a tailored approach that considers the patient's status to optimize dialysis delivery.